MCM3 and Ki67 proliferation markers in odontogenic cysts and ameloblastoma - Zohreh Jaafari-Ashkavandi; Fatemeh Mehranmehr; Elham Roosta (Elsevier, 2019)
Background: MCM3 is a marker of proliferation that has been used as a diagnostic or prognostic marker in many pathologic lesions. Purpose: The purpose of this study is to investigate the proliferative activity of dentigerous cysts, odontogenic keratocyst and ameloblastoma using minichromosome maintenance 3 (MCM3) and compare it with Ki-67 proliferation marker. Methods: In this cross-sectional study, 40 cases including 11 cases of dentigerous cyst, 14 odontogenic keratocyst, and 15 ameloblastoma were included. Immunohistochemical expression of MCM3 and Ki-67 were investigated and compared statistically using ANOVA, Chi-square, Tukey and Spearman's correlation tests. Results: All subjects were positive for Ki-67 and MCM3. There was a significant difference in MCM3 and Ki-67 expression among all groups. Compared to Ki-67, MCM3 exhibited a higher level of expression. Ameloblastoma and odontogenic keratocyst revealed higher expression rate of both markers in comparison to dentigerous cysts. Conclusion: The results showed MCM3 and Ki67 expression in the most common odontogenic cysts and tumors, especially more aggressive lesions. MCM3 might have a role in pathogenesis of these lesions and could be a reliable marker for assessing proliferation activity.